Alteration of enzyme activities and MYb10 gene expression in response to brown rot disease in two apple cultivars - Mohammad Reza Raji; Sepideh Sanjari; Fatemeh Derikvand; Mitra Khademi; Mostafa Farajpour (Biochemistry and Biophysics Reports, 2025)
Apples (Malus domestica) are widely enjoyed but are prone to fungal infections, notably brown rot caused by Monilinia spp., which significantly impacts postharvest quality. This study evaluated the activities of catalase (CAT), peroxidase (POD), phenylalanine ammonia lyase (PAL), and polyphenol oxidase (PPO), along with the expression of MdMYB10 in two apple cultivars (Gala Imperial and Lebanese) after inoculation with Monilinia laxa over 1, 2, and 7 days. Results showed that enzyme activities and MdMYB10 expression significantly increased post-infection, indicating their roles in the defense against brown rot. Notably, a strong positive correlation was found between MdMYB10 upregulation and the activities of PAL, POD, and PPO. PAL activity peaked at 2 days post-inoculation, while MdMYB10 expression, along with POD and PPO activities, reached their highest levels by day 7. These findings suggest that MdMYB10 expression enhances the activities of these defense enzymes, with PAL initiating the response by producing phenolic compounds that serve as substrates for PPO and POD, aiding in disease resistance. Although PAL, POD, and PPO activities increased after M. laxa inoculation, no significant differences in PPO and POD activities were observed between cultivars, while Gala Imperial displayed higher PAL activity, enhancing its resistance to infection. The study highlights MdMYB10 as a potential candidate for breeding programs aimed at improving brown rot resistance in apples.